ON THE ROLE OF ZOOPLANKTON IN THE NUTRITION OF CARP FRY - Mitra, G N; Mohapatra, P (Indian Journal of Fisheries, 2015)
In order to stock their tanks fish farmers in Orissa now depend on fish-seed, collected from the major rivers during floods, coii|isting mainly of Catla catla (Ham.), Labeo rohita (Ham.), Cirrhiria mrigala (Ham.), Labeo calbasu (Ham.), Labeo bata (Ham.), Cinhina rebd (Ham.) and several other species. The fish-seed, at the time of collection, vary in length from 5 to 7 mm., and is often-found with yolk-sac not fully absorbed. The mixed fish-seed has to be reared at least to the size of about 30 mm. in length, in specially prepared nursery tanks, before transplantation into'th^stocking tanks. It has generally been established by Welch (1935), Birge (1945), Hall (1949), AUkunhi (1952) and several other authors that carp fry in their early stages depend exclusively on zooplankton, mostly Entomostraca, for food. Harman (1950) has observed that algae will do no harm to the fishes, provided they do not become too abundant in the pond. Alikunhi et al. (1951) have found dense algal blooms positively harmful to carp fry in nursery tanks, affecting their rate of survival adversely. Mookerjee (1944-45) and Hora (1943) have observed that phytoplankton serve as food for caip fry in their early stages; Mookerjee has, in fact, stated that 5-10 mm.-long fry of the major Indian carps feed exclusively on unicellular algae.